Pertimbangan Hakim Terhadap Perbuatan Melawan Hukum oleh Ahli Waris Dalam Pinjam-Meminjam Uang yang Akan Digunakan Untuk Investasi Penitipan dan Bisnis Beras (Studi Putusan Nomor: 222/Pdt.G/2022/PN TJK) - Erlina Bachri; Intan Nurina Seftiniara; Saniyya Fadhilah Agustine (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Lending and borrowing can be done through an agreement between the borrower and the lender in the form of an agreement. The loan agreement can be in the form of money or goods with an agreement to replace the amount of the same value as the loan. However, many violate this agreement, resulting in losses for one of the parties. This loss is the basis for the cause of Unlawful Acts. Factors Causing Unlawful Acts in Loan Agreements Based on Decision Number: 222/Pdt.G/2022/PN TJK are: First, the existence of bad intentions or bad faith from one of the parties; Second, negligence (culpa) or deliberate action (dolus) by Iwan Palera Rindas; and Third, the trust factor where the Plaintiff was willing to lend such a large amount of money because of his personal relationship with the late Iwan Palera Rindas, whom he trusted like family. The Judge's Consideration of the Unlawful Acts in the Loan Agreement Based on Decision Number 222/Pdt.G/2022/PN TJK was correct and proper because it considered three legal aspects: first, Juridical Consideration, in this case Article 1100 of the Civil Code and Article 1365 of the Civil Code as the legal basis for the lawsuit; second, Philosophical Consideration, which considered the Plaintiff's ability to prove a legal relationship between the Plaintiff and the heirs of the late Iwan Palera Rindas, who were entrusted with money for the rice business; and third, Sociological Consideration, namely that the Defendants had not fulfilled their obligations as heirs of the late Iwan Palera Rindas by failing to return the Plaintiff's money amounting to Rp2,496,000,000.00 (two billion four hundred ninety-six million Rupiah).